Chile : studies on the social dimensions of globalization - Reinecke, Gerhard (ILO GenevaCH, 2001)
Provides a brief description of the trade and investment liberalization process followed by the key labour and social developments recorded since 1985. Sheds light on the link between trade patterns and the labour and social developments in question. Addresses the policies and conditions that will be needed to consolidate the gains from globalization, while making the process socially sustainable.